2024 Plan Approval: Independent Advisory and Evaluation Service & Supported Independent Bodies - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2024)
Through an intersessional decision on 22 December 2023, CGIAR System Council approved the consolidated 2024 workplan and budget (Scenario 2) of CGIAR’s Independent Advisory and Evaluation Service (IAES) and supported independent bodies, comprising the plans of ISDC, SPIA and the independent evaluation function implemented by IAES (Decision Reference SC/M19/EDP2).